Roberts-SC Phocomelia Syndrome (Pseudothalidomide Syndrome): A Case Report. - Ilana Naghi; Babak Behnam (Tehran University of Medical Sciences, 2013)
A 39-year-old pregnant woman at 38 weeks of gestation was referred with labor pain to a hospital. She had consanguinity with her husband. A female newborn had multiple craniofacial anomalies and phocomelia in right upper limb. The disease locus was assigned to chromosome17q21. Four days later, infant died of cardiopulmonary arrest.